Prediction of athletic performance of male and female athletes measured by triple hop for distance - Cesar, Guilherme M.; Edwards, Hannah T.; Hasenkamp, Ryan M.; Burnfield, Judith M. (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Triple hop for distance (THD) is an inexpensive test used clinically to evaluate lower extremity functional performance. Given known relationships between THD and lower extremity strength and power, THD could be used as a time efficient approach for assessing athleticism. Aim of Study. The aim of this study was to detect the extent to which THD of the dominant and non-dominant legs predict performance of vertical jump (VJ), pro-agility shuttle run, and 10-yard sprint in a large cohort of male and female collegiate athletes. Material and Methods. One hundred sixty athletes (80 men) performed VJ, 10-yard sprint, pro-agility shuttle run, and THD. Separate stepwise linear regression analyses were used to determine how THD of dominant and non-dominant legs predicted athletic performance of each test. Results. For male athletes, nondominant leg was the best and only predictor for VJ, pro-agility shuttle run, and 10-yard sprint, explaining 42.4%, 56.6%, and 46.9% of the variance, respectively. For female athletes, the dominant leg was the best and only predictor for VJ, pro-agility shuttle run, and 10-yard sprint, explaining 42.9%, 41.5%, and 27.0% of the variance, respectively. Conclusions. THD could serve as efficient tool to predict performance on athletic tasks including jumping and sprinting. Moreover, THD could guide subsequent training interventions aimed at improving athletes’ jumping and sprinting abilities
Keywords: agility; athletic performance; sprint; triple hopfor distance; vertical jump